Mediation of work-family support and affective commitment between family supportive supervisor Behaviour and workplace deviance - Siyuan Lei; Yangzi Zhang; Kenny S.L. Cheah (Heliyon, 2023)
Employees' Workplace Deviant Behavior (WDB) is an organizational threat to its sustainability. This study examines the impact of the supervisors’ role in improving organizational behavior because of the gap in the body of knowledge indicating the inconsistency, paucity, and uncertainties of relationships between variables when relating to their underpinning theories. The conceptualized model consists of the impact of family supportive supervisor behavior (FSSB) on workers' workplace deviant behavior (WDB) while considering Affective Commitment and Work-Family Supportive Behavior Attribution between the key variables. In terms of methodology, this quantitative study analyzed 321 valid surveys through descriptive and inferential statistics to ascertain if FSSB negatively impacts employees' WDB. As findings and novelty of this study, FSSB is found to negatively affect employees' WDB, while affective commitment mediates between FSSB and employees' WDB. Work-family supportive behavior attribution and personal life attribution of employees moderated the negative relationship between affective commitment and WDB, while work productivity attribution of employees had no significant effect as a moderator. With three (out of four) hypotheses supported by empirical evidence, this research has broadened previous studies of workers' WDB and offers organizations theoretical and practical recommendations for managing employees' WDB. More studies could be conducted in the future to address limitations in this research, examine other related theories in a new context, location, and/or culture, or select other suitable research methods.